Manufacturing method of electric storage element and electric storage element
The manufacturing method for electric storage elements, which involves dissolving a gas in the electrolyte within a sealed case to maintain negative pressure, addresses the issue of electrode distance increase and metallic lithium deposition, enhancing the stability and performance of these elements.
Patent Information
- Application Number
- JP2021540955
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-20
- Filing Date
- 2020-08-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-08-19
AI Technical Summary
In electric storage elements like lithium-ion batteries, the initial charge and discharge can lead to gas generation, causing the distance between electrodes to increase, resulting in uneven currents and metallic lithium deposition.
A manufacturing method for electric storage elements involves accommodating an electrode body with stacked negative and positive electrodes, an electrolyte, and a gas soluble in the electrolyte within a sealable case. The case is then sealed while the gas is dissolved in the electrolyte, creating a negative pressure atmosphere that dissolves gases between the electrodes, preventing their accumulation and the resulting increase in electrode distance.
This method effectively suppresses the increase in electrode distance, reducing the likelihood of metallic lithium deposition and improving the stability and performance of electric storage elements.
Smart Images

Figure 0007647557000002 
Figure 0007647557000003 
Figure 0007647557000004
Abstract
Description
[Technical Field]
[0001] The present invention relates to a method for manufacturing an energy storage element and to an energy storage element. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries, typified by lithium-ion non-aqueous electrolyte secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The non-aqueous electrolyte secondary batteries generally include an electrode assembly having a pair of electrodes electrically isolated by a separator, and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring ions between the electrodes. In addition to non-aqueous electrolyte secondary batteries, capacitors such as lithium-ion capacitors and electric double layer capacitors are also widely used as energy storage elements.
[0003] With the aim of improving the characteristics of such electricity storage elements, such as the capacity retention rate, many studies have been conducted on additives to electrolyte solutions, for example (see Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 2007-165125 Summary of the Invention [Problem to be solved by the invention]
[0005] However, depending on the additives in the electrolyte, the additives may decompose during the initial charge / discharge, generating gases such as carbon monoxide. When gas is generated during this initial charge / discharge, gas accumulation occurs between the electrodes, making it easier for the inter-electrode distance to increase in some areas. This can lead to current unevenness and the risk of metallic lithium deposition occurring in areas where the inter-electrode distance has increased. Furthermore, even if the electrolyte does not contain additives, gas generation due to oxidation-reduction decomposition of the electrolyte can also increase the inter-electrode distance in some areas.
[0006] The present invention has been made in light of the above circumstances, and has an object to provide a method for manufacturing an energy storage element that can prevent the inter-electrode distance from becoming large, and an energy storage element. [Means for solving the problem]
[0007] A method for manufacturing a storage element according to one aspect of the present invention, which has been made to solve the above problem, includes housing an electrode body in which a negative electrode and a positive electrode are stacked in a case, housing an electrolyte solution in the case, housing the electrolyte solution in the case, and then housing a gas soluble in the electrolyte solution in the case, and sealing the case with the gas soluble in the electrolyte solution housed in the case.
[0008] Another aspect of the present invention provides an energy storage element comprising an electrode body in which a negative electrode and a positive electrode are stacked, an electrolyte, a gas soluble in the electrolyte, and a sealable case for containing the electrode body, the electrolyte, and the gas, the interior of which has a negative pressure atmosphere. [Effects of the Invention]
[0009] According to the present invention, it is possible to provide a method for manufacturing an energy storage element that can prevent the inter-electrode distance from becoming large, and an energy storage element. [Brief explanation of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic exploded perspective view showing an energy storage element according to one embodiment of the present invention. [Figure 2] FIG. 2 is a schematic cross-sectional view of an energy storage element according to one embodiment of the present invention. [Figure 3] FIG. 3 is a schematic diagram showing an electricity storage device configured by assembling a plurality of electricity storage elements according to one embodiment of the present invention. [Figure 4] FIG. 4 is a cross-sectional image of an electrode body of an energy storage element according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0011] A method for manufacturing a storage element according to one aspect of the present invention includes housing an electrode body in which a negative electrode and a positive electrode are stacked in a case, housing an electrolyte solution in the case, housing the electrolyte solution in the case, and then housing a gas soluble in the electrolyte solution in the case, and sealing the case with the gas soluble in the electrolyte solution housed in the case.
[0012] The manufacturing method of the energy storage element, which includes the above steps, can manufacture an energy storage element that is highly effective in suppressing the occurrence of metallic lithium electrodeposition, which occurs when the inter-electrode distance increases during the initial charge / discharge cycle due to the decomposition of additives or the redox decomposition of the electrolyte. While the reason for this is unclear, it is believed to be as follows: In an energy storage element, gas is generally generated within the case due to the decomposition of additives or the redox decomposition of the electrolyte during the initial charge / discharge cycle. When this gas is generated between the electrodes, the presence of this gas causes gas accumulation between the electrodes, increasing the inter-electrode distance. This can lead to current unevenness and the occurrence of metallic lithium electrodeposition near the increased inter-electrode distance. However, in the manufacturing method of the energy storage element, after the electrolyte solution is placed in the case, a gas soluble in the electrolyte solution is placed in the case, and the case is sealed with the gas contained in the case. This allows the gas to dissolve in the electrolyte after sealing. As a result, the pressure inside the case decreases, creating a negative pressure inside the case, i.e., a force pulling the case inward is generated, causing the gas present between the electrodes to be expelled from the electrode body. Therefore, it is presumed that the method for manufacturing an energy storage element can prevent the distance between electrodes from increasing, and therefore can manufacture an energy storage element that can prevent the occurrence of metal lithium electrodeposition.
[0013] In the present invention, the term "gas soluble in the electrolyte" refers to a gas soluble in 1 cm of electrolyte at 25°C under 1 atmosphere. 3 The solubility of a gas in 1cm 3 The above gases.
[0014] The electrode body is a wound-type electrode body having a pair of opposing curved portions and a flat portion located between the pair of curved portions. When, after the electrode body is accommodated and before the sealing, the electrode body has a hollow region in the center as viewed from the winding axis direction, or a gap exists between the outer surface of the flat portion of the electrode body and the inner surface of the case, or a combination thereof, the effects of the manufacturing method for the energy storage element can be more effectively achieved. Thus, when the wound-type electrode body has a pair of opposing curved portions and a flat portion located between the pair of curved portions, and when, after the electrode body is accommodated and before the sealing, the electrode body has a hollow region in the center as viewed from the winding axis direction, or a gap exists between the outer surface of the flat portion of the electrode body and the inner surface of the case, or a combination thereof, the flat portion of the electrode body is likely to have an inter-electrode distance expanding toward the hollow region in the center or the gap on the outer surface side of the flat portion. Therefore, gas generated in these spaces by decomposition of additives or oxidation-reduction decomposition of the electrolyte during the initial charge / discharge cycle is likely to increase the inter-electrode distance, making metallic lithium electrodeposition more likely to occur. According to the method for manufacturing an energy storage element, even in such a case, it is possible to manufacture an energy storage element that is highly effective in suppressing the occurrence of metal lithium electrodeposition that occurs when the inter-electrode distance increases.
[0015] It is preferable that the main component of the electrolyte solution is carbonate and the gas is carbon dioxide. When the main component of the electrolyte solution is carbonate, using carbon dioxide as the gas can increase the solubility of the gas in the electrolyte solution. Here, the "main component" refers to a component that is contained in an amount of, for example, 50% by mass or more of the total mass of the electrolyte solution.
[0016] The electrolyte preferably contains an oxalate complex salt. Among additives used in the electrolyte, the oxalate complex salt generates a large amount of gases that are difficult to dissolve in the electrolyte, such as carbon monoxide, during the initial charge / discharge. This makes it easier for gases such as carbon monoxide to accumulate between the electrodes, increasing the distance between the electrodes. According to the method for producing an energy storage element, even in such a case, it is possible to produce an energy storage element that effectively suppresses the increase in the distance between the electrodes.
[0017] It is preferable that the case has a flat, bottomed, rectangular tubular case body and a lid, and that after the case is sealed, the electrode body directly or indirectly contacts the inner surface of the case body. Because the case body has a flat, bottomed, rectangular tubular shape, when the inside of the case is in a negative pressure state, a force pulling the case inward is generated, making the side of the case body more likely to become concave. Because the electrode body directly or indirectly contacts the inner surface of the case body, the side of the electrode body facing the side of the case body that is concave due to the negative pressure is pressurized in the thickness direction, making it easier for gas between the electrodes to be discharged outside the electrode body. Therefore, the effect of suppressing the increase in the inter-electrode distance can be further enhanced.
[0018] Preferably, the manufacturing method of the energy storage element further comprises housing a member capable of adsorbing the gas in the case. By further comprising housing a member capable of adsorbing the gas in the case, the amount of gas absorbed increases and the negative pressure inside the case also increases, making it easier for the gas between the electrodes to be discharged outside the electrode body, thereby further improving the effect of suppressing an increase in the inter-electrode distance. Furthermore, because the gas is also absorbed by the adsorbable member, the time it takes for the inside of the case to become a negative pressure atmosphere after the case is sealed can be shortened.
[0019] Another aspect of the present invention provides an energy storage element comprising an electrode body in which a negative electrode and a positive electrode are stacked, an electrolyte, a gas soluble in the electrolyte, and a sealable case for containing the electrode body, the electrolyte, and the gas, the interior of which has a negative pressure atmosphere.
[0020] According to the energy storage element, by providing the above configuration, after the electrolyte solution is accommodated in the case, a gas soluble in the electrolyte solution is accommodated in the case, and the case is sealed, whereby the gas dissolves in the electrolyte solution. As a result, the pressure inside the case decreases, and the interior of the case becomes negative pressure, i.e., a force pulling the case inward is generated, causing the gas present between the electrodes to be discharged to the outside of the electrode body. Therefore, the energy storage element is highly effective in suppressing the occurrence of metallic lithium electrodeposition because the increase in the inter-electrode distance is suppressed. Here, the "atmosphere" refers to the gas accommodated in the surplus space inside the case. Furthermore, "the interior of the case has a negative pressure atmosphere" refers to the pressure in the surplus space inside the case being lower than the pressure outside the case.
[0021] A method for manufacturing an electric storage element according to the present invention will be described in detail below. As an example of a method for manufacturing an electric storage element, a method for manufacturing a non-aqueous electrolyte secondary battery (particularly a lithium ion secondary battery) will be described, but this is not intended to limit the scope of application of the present invention.
[0022] <Method of manufacturing an energy storage element> A method for manufacturing an energy storage element according to one embodiment of the present invention includes the steps of housing an electrode assembly, in which a negative electrode and a positive electrode are stacked, in a case (hereinafter also referred to as the electrode assembly housing step), housing an electrolyte solution in the case (hereinafter also referred to as the electrolyte solution housing step), housing a gas soluble in the electrolyte solution in the case after housing the electrolyte solution in the case (hereinafter also referred to as the gas housing step), and sealing the case with the gas soluble in the electrolyte solution housed in the case (hereinafter also referred to as the sealing step). Preferably, the method for manufacturing an energy storage element further includes housing a member capable of adsorbing the gas in the case (hereinafter also referred to as the adsorption member housing step). Furthermore, the method for manufacturing an energy storage element may include other steps, such as forming a negative electrode (hereinafter also referred to as the negative electrode forming step), forming a positive electrode (hereinafter also referred to as the positive electrode forming step), and forming an electrode assembly (hereinafter also referred to as the electrode assembly forming step).
[0023] [Negative electrode formation process] In the negative electrode forming step, a negative electrode having a negative electrode substrate and a negative electrode mixture layer is formed. In the negative electrode forming step, a negative electrode mixture containing a negative electrode active material is applied to the negative electrode substrate, so that the negative electrode mixture can be disposed along at least one surface of the negative electrode substrate. Specifically, for example, the negative electrode mixture is applied to the negative electrode substrate and then dried to form the negative electrode mixture layer.
[0024] The negative electrode substrate is a substrate having electrical conductivity. Metals such as copper, nickel, stainless steel, and nickel-plated steel, or alloys thereof, are used as the material for the negative electrode substrate, with copper or a copper alloy being preferred. The negative electrode substrate may be in the form of a foil, a vapor-deposited film, or the like, with foil being preferred from the standpoint of cost. That is, copper foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil. Having "electrical conductivity" means that the volume resistivity measured in accordance with JIS-H0505 (1975) is 1×10 7 This means that the resistance is Ω·cm or less.
[0025] The negative electrode mixture that forms the negative electrode mixture layer contains optional components such as a conductive agent, a binder, a thickener, and a filler as needed.
[0026] The negative electrode active material is usually a material capable of absorbing and releasing lithium ions. Specific examples of the negative electrode active material include metals or semimetals such as Si and Sn, metal oxides or semimetal oxides such as Si oxide and Sn oxide, polyphosphate compounds, carbon materials such as graphite and non-graphitic carbon (easily graphitizable carbon or non-graphitizable carbon), and lithium metal composite oxides such as lithium titanate.
[0027] Furthermore, the negative electrode mixture may contain typical non-metallic elements such as B, N, P, F, Cl, Br, and I; typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, and Ge; and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W.
[0028] Examples of the conductive agent include carbonaceous materials, metals, and conductive ceramics. Examples of carbonaceous materials include graphitized carbon, non-graphitized carbon, and graphene-based carbon. Examples of non-graphitized carbon include carbon nanofibers, pitch-based carbon fibers, and carbon black. Examples of carbon black include furnace black, acetylene black, and ketjen black. Examples of graphene-based carbon include graphene, carbon nanotubes (CNTs), and fullerenes. The conductive agent may be in the form of powder or fiber. As the conductive agent, one of these materials may be used alone, or two or more may be mixed and used. These materials may also be used in combination. For example, a composite material of carbon black and CNTs may be used. Among these, carbon black is preferred from the viewpoints of electronic conductivity and coatability, and acetylene black is particularly preferred.
[0029] Examples of the binder include elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), and fluororubber; thermoplastic resins other than elastomers such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, and polyimide; and polysaccharide polymers.
[0030] Examples of the thickener include polysaccharide polymers such as cellulose derivatives, such as carboxymethyl cellulose (CMC), methyl cellulose (MC), cellulose acetate phthalate (CAP), hydroxypropyl methyl cellulose (HPMC), hydroxypropyl methyl cellulose phthalate (HPMCP), etc. In addition, when the thickener has a functional group that reacts with lithium, it is preferable to deactivate this functional group in advance by methylation or the like.
[0031] The filler is not particularly limited, and examples of the main component of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, sparingly soluble ionic crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, substances derived from mineral resources such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof.
[0032] The negative electrode mixture may be a negative electrode mixture paste containing a dispersion medium in addition to the optional components described above, such as an aqueous solvent such as water or a mixed solvent mainly containing water, or an organic solvent such as N-methylpyrrolidone or toluene.
[0033] The negative electrode mixture layer may be laminated directly on the negative electrode substrate or via an intermediate layer. The configuration of the intermediate layer is not particularly limited and may be formed, for example, from a composition containing a resin binder and conductive particles. Furthermore, a negative electrode overcoat layer containing at least inorganic particles and a binder may be provided on the upper surface of the negative electrode mixture layer. The provision of the negative electrode overcoat layer provides effects such as improved ionic conductivity and reduced risk of short circuiting.
[0034] [Positive electrode formation process] In the positive electrode formation step, a positive electrode having a positive electrode substrate and a positive electrode mixture layer is formed. In the positive electrode formation step, a positive electrode mixture containing a positive electrode active material is applied to the positive electrode substrate, so that the positive electrode mixture can be disposed along at least one surface of the positive electrode substrate. Specifically, for example, the positive electrode mixture is applied to the positive electrode substrate and dried to form the positive electrode mixture layer. In addition, the positive electrode mixture may be a positive electrode mixture paste that further contains a dispersion medium in addition to the optional components described above. The dispersion medium can be selected from any of those exemplified in the negative electrode formation step.
[0035] The positive electrode substrate is electrically conductive. Examples of the material for the substrate include metals such as aluminum, titanium, tantalum, and stainless steel, or alloys thereof. Among these, aluminum and aluminum alloys are preferred because of their balance of high potential resistance, high conductivity, and cost. Examples of the form of the positive electrode substrate include foil and vapor-deposited film, with foil being preferred from the standpoint of cost. In other words, aluminum foil is preferred as the positive electrode substrate. Examples of aluminum or aluminum alloys include A1085 and A3003 as specified in JIS-H4000 (2014).
[0036] The positive electrode mixture that forms the positive electrode active material layer contains optional components such as a conductive agent, a binder, a thickener, and a filler, as required.
[0037] The positive electrode active material can be appropriately selected from, for example, known positive electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the positive electrode active material for a lithium ion secondary battery. Examples of the positive electrode active material include lithium transition metal composite oxides having an α-NaFeO2 crystal structure, lithium transition metal oxides having a spinel crystal structure, polyanion compounds, chalcogen compounds, sulfur, and the like. Examples of lithium transition metal composite oxides having an α-NaFeO2 crystal structure include Li[Li x Ni 1-x ]O2(0≦x<0.5), Li[Li x NiγCo (1-x- gamma ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Co (1-x) ]O2(0≦x<0.5), Li[Li x NiγMn (1-x- gamma ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x NiγMnβCo (1-x- gamma - β ) ]O2(0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), Li[Li x NiγCoβAl(1-x- gamma - β ) ]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1). Examples of lithium transition metal oxides with spinel crystal structures include Li x Mn2O4, Li x NiγMn (2- gamma ) Examples of polyanion compounds include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, and Li2CoPO4F. Examples of chalcogen compounds include titanium disulfide, molybdenum disulfide, and molybdenum dioxide. Atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer, one of these materials may be used alone, or two or more may be mixed and used. In the positive electrode mixture layer, one of these compounds may be used alone, or two or more may be mixed and used.
[0038] The conductive agent is not particularly limited as long as it is a conductive material, and can be selected from the materials exemplified in the negative electrode forming step.
[0039] Examples of the binder include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, and polyimide; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), and fluororubber; and polysaccharide polymers.
[0040] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC), methyl cellulose, etc. In addition, when the thickener has a functional group that reacts with lithium, it is preferable to deactivate this functional group in advance by methylation or the like.
[0041] The filler can be selected from the materials exemplified in the negative electrode forming step.
[0042] The positive electrode mixture layer may be laminated directly on the positive electrode substrate or via an intermediate layer. The intermediate layer is a coating layer on the surface of the positive electrode substrate, and contains conductive particles such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. As with the negative electrode, the configuration of the intermediate layer is not particularly limited and can be formed, for example, from a composition containing a resin binder and conductive particles.
[0043] [Electrode body formation process] In the electrode body forming step, the positive electrode and the negative electrode are used to form an electrode body. The electrode body is preferably a wound electrode body having a pair of opposing curved portions and a flat portion located between the pair of curved portions. In the electrode body forming step, the positive electrode and the negative electrode are stacked or wound via a separator described later to form an electrode body in which the positive electrode and the negative electrode are alternately stacked.
[0044] Examples of materials that can be used for the separator include woven fabric, nonwoven fabric, and porous resin film. Among these, porous resin film is preferred from the viewpoint of strength, and nonwoven fabric is preferred from the viewpoint of nonaqueous electrolyte retention. As the main component of the separator, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of strength, and polyimide and aramid are preferred from the viewpoint of resistance to oxidative decomposition. These resins may also be combined. Alternatively, a composite separator having a porous resin film and an inorganic porous layer may be used.
[0045] The effects of the manufacturing method for the energy storage element can be more effectively achieved when, after the electrode assembly is accommodated and before the sealing, the electrode assembly has a hollow region in the center as viewed from the winding axis direction, or a gap exists between the outer surface of the flat portion of the electrode assembly and the inner surface of the case, or a combination thereof. Thus, when the wound electrode assembly has a pair of opposing curved portions and a flat portion located between the pair of curved portions, and after the electrode assembly is accommodated and before the sealing, the electrode assembly has a hollow region in the center as viewed from the winding axis direction, or a gap exists between the outer surface of the flat portion of the electrode assembly and the inner surface of the case, or a combination thereof, the flat portion of the electrode assembly is likely to have an inter-electrode distance that increases toward the hollow region in the center or the gap on the outer surface side of the flat portion. Therefore, in these spaces, gas generated by decomposition of additives or oxidation-reduction decomposition of the electrolyte during the initial charge / discharge cycle is likely to increase the inter-electrode distance, making metallic lithium electrodeposition more likely to occur. According to the method for manufacturing an energy storage element, even in such a case, it is possible to manufacture an energy storage element that is highly effective in suppressing the occurrence of metal lithium electrodeposition that occurs when the inter-electrode distance increases.
[0046] [Electrode body accommodation process] In the electrode assembly housing step, the electrode assembly in which the negative electrode and the positive electrode are stacked is housed in a case. The case may be a known metal case, a resin case, or the like, commonly used for non-aqueous electrolyte secondary batteries. The metal may be, for example, aluminum or an aluminum alloy. The case may have, for example, a case body and a lid that can close the opening of the case body.
[0047] When the case has a flattened, bottomed, rectangular tubular case body and a lid, the electrode body preferably directly or indirectly contacts the inner surface of the case body after the case is sealed. Because the case body has a flattened, bottomed, rectangular tubular shape, when the interior of the case is under negative pressure, a force pulling the case inward is generated, making the side of the case body more likely to become concave. When the electrode body directly or indirectly contacts the inner surface of the case body, the side of the electrode body facing the side of the case body that is concave due to negative pressure is pressurized in the thickness direction, making it easier for gas between the electrodes to be discharged outside the electrode body. Therefore, the effect of suppressing an increase in the inter-electrode distance can be further enhanced. An example of a case in which the electrode body is indirectly contacting the inner surface of the case body is when the energy storage element includes a spacer, sheet, etc. interposed between the case and the electrode body, and the inner surface of the case is indirectly contacting the outer surface of the electrode body via the spacer, sheet, etc. The material of the spacer, sheet, etc. is not particularly limited as long as it has insulating properties.
[0048] [Electrolyte containing process] In the electrolyte solution containing step, the electrolyte solution is contained in the case. When the energy storage element is a nonaqueous electrolyte secondary battery, a nonaqueous electrolyte solution is used as the electrolyte solution. The electrolyte solution can be contained by a known method. For example, in the case of the nonaqueous electrolyte secondary battery, the electrolyte solution is contained in the case by injecting the nonaqueous electrolyte solution through an inlet provided in the case.
[0049] (Non-aqueous electrolyte) The nonaqueous electrolyte may be a known nonaqueous electrolyte commonly used in general nonaqueous electrolyte secondary batteries (storage elements). The nonaqueous electrolyte contains a nonaqueous solvent and an electrolyte salt dissolved in the nonaqueous solvent.
[0050] As the non-aqueous solvent, a known non-aqueous solvent that is commonly used as a non-aqueous solvent for a general non-aqueous electrolyte for a storage element can be used. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, esters, ethers, amides, sulfones, lactones, nitriles, etc. Among these, it is preferable to use at least a cyclic carbonate or a chain carbonate, and it is more preferable to use a combination of a cyclic carbonate and a chain carbonate.
[0051] Examples of the cyclic carbonate include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, catechol carbonate, 1-phenylvinylene carbonate, and 1,2-diphenylvinylene carbonate, and among these, EC or PC is preferred.
[0052] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diphenyl carbonate, and among these, DMC or EMC is preferred.
[0053] The electrolyte salt may be any known electrolyte salt commonly used in non-aqueous electrolyte solutions for general energy storage devices, including lithium salts, sodium salts, potassium salts, magnesium salts, and onium salts, with lithium salts being preferred.
[0054] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, and lithium salts having a hydrocarbon group in which hydrogen is substituted with fluorine, such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.
[0055] (additives) Various additives may be added to the electrolyte solution in order to improve the performance of the electricity storage element, as long as the effects of the present invention are not impaired.
[0056] When the electrolyte is a non-aqueous electrolyte, additives that are generally used in non-aqueous electrolyte secondary batteries can be used as the additive, and examples thereof include oxalate complex salts, boric acid esters, aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partially fluorinated compounds of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; fluorine-containing anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; vinylene carbonate, methylvinylene carbonate, ethylvinylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, trifluoropropylene carbonate, succinic anhydride, glutaric anhydride, maleic anhydride, and the like. Examples of the non-aqueous electrolyte include methyl toluenesulfonate, methyl toluenesulfonate, dimethyl sulphite, ethylene sulphite, propane sultone, propene sultone, butane sultone, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulphate, ethylene sulphate, sulfolane, dimethyl sulphone, diethyl sulphone, dimethyl sulphoxide, diethyl sulphoxide, tetramethylene sulphoxide, diphenyl sulphide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulphide, dipyridinium disulphide, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, and tetrakistrimethylsilyl titanate. These may be added to the non-aqueous electrolyte either alone or in combination.
[0057] Among the additives, oxalate complex salts generate a large amount of gases that are insoluble in the electrolyte, such as carbon monoxide, during the initial charge / discharge cycle. This makes it easier for gases such as carbon monoxide to accumulate between the electrodes, resulting in a partial increase in the inter-electrode distance. Even in such cases, the manufacturing method for an energy storage device can produce an energy storage device that effectively suppresses the increase in inter-electrode distance. Examples of the oxalate complex salts include lithium difluorobisoxalate phosphate [LiPF2(C2O4)2], lithium difluorooxalate borate [LiBF2(C2O4)], lithium bisoxalate borate [LiB(C2O4)2], lithium tetrafluorooxalate phosphate [LiPF4(C2O4)], and lithium trisoxalate phosphate [LiP(C2O4)3]. Among these, lithium difluorobisoxalate phosphate generates a large amount of gases that are insoluble in the electrolyte, such as carbon monoxide, thereby enhancing the effectiveness of the manufacturing method for an energy storage device.
[0058] [Gas storage process] In the gas containing step, after the electrolyte containing step, a gas soluble in the electrolyte is contained in the case. Specifically, after the electrolyte is contained in the case, the gas is injected into the case through the inlet, thereby containing the gas soluble in the electrolyte in the case. The gas may be injected under reduced pressure inside the case using a vacuum pump or the like. Here, "under reduced pressure" means, for example, that the pressure in the excess space inside the case is less than atmospheric pressure. The inlet may be provided separately from the inlet for injecting the electrolyte. As described above, the energy storage element disclosed herein includes the electrolyte solution, the gas, and the case, and the inside of the case has a negative pressure atmosphere. One suitable condition for realizing such a negative pressure atmosphere is to first house the electrolyte solution in the case, and then house the gas in the case. In this way, by injecting the gas into the case in which the electrolyte solution is housed, the gas dissolves in the electrolyte solution after sealing, effectively reducing the pressure inside the case, and the inside of the case can be placed in a suitable negative pressure state. On the other hand, in an embodiment in which the gas is accommodated in the case and then the electrolyte solution is poured into the case, much of the gas dissolves in the electrolyte solution during the pouring process, and the gas becomes too soluble in the electrolyte solution before sealing (for example, becomes saturated). If too much gas dissolves in the electrolyte solution before sealing, it becomes difficult for the gas to further dissolve in the electrolyte solution after sealing, and there may be cases in which the pressure inside the case cannot be effectively reduced. Preferably, after the electrolyte solution is placed in the case, pre-charging is performed before sealing. Then, after the pressure inside the case is reduced using a vacuum pump, the gas is injected so that the pressure is close to atmospheric pressure. The pressure immediately after gas injection is an important factor from the viewpoint of creating a suitable negative pressure atmosphere inside the case. Preferably, the gas is injected so that the pressure immediately after gas injection is 0.1 MPa or more and 0.2 MPa or less (more preferably 0.1 MPa or more and 0.15 MPa or less, even more preferably 0.1 MPa or more and 0.12 MPa or less, and particularly preferably 0.1 MPa or more and 0.11 MPa or less). Injecting the gas so that the pressure immediately after gas injection is close to atmospheric pressure can eliminate or mitigate the problem of excessive dissolution of the gas in the electrolyte solution before sealing, and can effectively reduce the pressure inside the case after sealing.
[0059] From the viewpoint of further reducing the pressure inside the case, the amount of the gas soluble in the electrolyte solution is preferably 40% by volume or more, more preferably 70% by volume or more, and may be, for example, 95% by volume or more, relative to the volume of the excess space inside the case. The amount of the gas soluble in the electrolyte solution may be less than 100% by volume relative to the volume of the excess space inside the case. The technology disclosed herein can be preferably implemented in an embodiment in which the amount of the gas soluble in the electrolyte solution is 70% by volume or more and less than 100% by volume (preferably 80% by volume or more and 95% by volume or less) relative to the volume of the excess space inside the case. Here, the "volume of the excess space inside the case" refers to the volume obtained by subtracting the volumes of the electrode assembly, electrolyte, and structures such as the current collector from the internal volume of the case. Furthermore, the volume of the electrode assembly refers to the actual volume of the components of the electrode (active material, separator, etc.) and does not include voids present between the active materials or within the separator. In other words, the volume of the excess space inside the case means the volume of gas that can be accommodated inside the case at 25°C and atmospheric pressure.
[0060] The content of the gas soluble in the electrolyte solution contained in the case is preferably 80% by volume or more, more preferably 98% by volume or more, and even more preferably 100% by volume, based on the total volume of gas contained in the case, from the viewpoint of reducing the pressure inside the case. From the viewpoint of ease of handling the gas, the content of the gas soluble in the electrolyte solution may be 80% by volume or less, based on the total volume of gas contained in the case.
[0061] When the electrolyte is a non-aqueous electrolyte containing carbonate as a main component, examples of the gas soluble in the non-aqueous electrolyte include carbon dioxide gas (1 cm of non-aqueous electrolyte at 25°C under 1 atmosphere). 3 Solubility in 5cm 3 When the electrolyte solution is a non-aqueous electrolyte solution containing carbonate as a main component, examples of the gas that is poorly soluble or insoluble in the non-aqueous electrolyte solution include oxygen gas, nitrogen gas, hydrogen, and methane.
[0062] When the main component of the electrolyte solution is carbonate, the gas is preferably carbon dioxide, which is easy to handle and obtain.
[0063] [Adsorption member accommodation process] Preferably, the manufacturing method of the energy storage element further includes an adsorption member accommodating step. In the adsorption member accommodating step, a member capable of adsorbing gas is accommodated in the case. By including the adsorption member accommodating step in the manufacturing method of the energy storage element, the amount of gas absorbed increases and the negative pressure inside the case also increases, making it easier for gas between the electrodes to be discharged outside the electrode body, thereby further improving the effect of suppressing an increase in the inter-electrode distance. Furthermore, because the adsorption member also absorbs the gas, the time required for the interior of the case to become a negative pressure atmosphere after the case is sealed can be shortened.
[0064] Examples of materials capable of adsorbing gas include silica, zeolite, activated carbon, alumina, etc. The above-mentioned materials can be housed as a core material placed in the center of the electrode body, a sheet or spacer placed between the electrode body and the case, or other materials.
[0065] [Sealing process] In the sealing step, the case is sealed while the gas soluble in the electrolyte is contained in the case. Specifically, after the gas is contained in the case, the injection port is sealed to obtain a nonaqueous electrolyte secondary battery. The injection port is sealed, for example, by closing the injection port with a sealing member and fixing the sealing member by laser welding or the like.
[0066] After sealing, the pressure inside the case when the dissolution of the gas into the electrolyte reaches equilibrium is preferably 0.02 MPa or more and 0.09 MPa or less at 25°C, from the viewpoint of effectively suppressing an increase in the distance between the electrodes. The pressure inside the case immediately after sealing is preferably 0.07 MPa or more and 0.10 MPa or less. In other words, most of the gas is not dissolved in the electrolyte immediately after sealing, and by dissolving the gas in the electrolyte after sealing, the pressure inside the case can be reduced.
[0067] The time that elapses between the time the gas soluble in the electrolyte is introduced and the time the injection port is sealed is preferably 1 hour or less, from the viewpoint of reducing the amount of gas that dissolves in the electrolyte before sealing or that diffuses out of the case through the injection port. The time is preferably 30 minutes or less (e.g., 1 minute to 30 minutes), more preferably 20 minutes or less, even more preferably 15 minutes or less, and particularly preferably 10 minutes or less (e.g., 5 minutes or less). By shortening the time that elapses between the time the gas soluble in the electrolyte is introduced and the time the injection port is sealed, the inconvenience of the gas being too dissolved in the electrolyte before sealing (typically, saturated dissolution) can be eliminated or alleviated, and the pressure inside the case can be effectively reduced after sealing.
[0068] After the gas is introduced into the case, the method may include a step of temporarily sealing the injection port before a step of sealing the injection port. The step of temporarily sealing the injection port is, for example, a step of temporarily blocking the injection port using a rubber plug member or the like. By including the step of temporarily sealing the injection port, it is possible to prevent the gas contained in the case from diffusing to the outside of the case through the injection port. In this case, the step of sealing the injection port may include removing the plug member or the like and then blocking the injection port with a sealing member, and fixing the sealing member by laser welding or the like. Furthermore, the step of sealing the injection port may include disposing a sealing member that covers the plug member or the like that blocks the injection port, and fixing the sealing member by laser welding or the like.
[0069] According to this method for manufacturing an energy storage element, an energy storage element can be manufactured that is highly effective in preventing the inter-electrode distance from becoming large.
[0070] <Energy storage element> The energy storage element includes an electrode assembly in which a negative electrode and a positive electrode are stacked, an electrolyte, a gas soluble in the electrolyte, and a sealable case for containing the electrode assembly, the electrolyte, and the gas. The interior of the case has a negative pressure atmosphere. The electrode assembly preferably forms a wound electrode assembly in which the stacked positive electrode and negative electrode are wound with a separator interposed therebetween. The electrolyte is impregnated in the separator and is interposed between the positive electrode and the negative electrode. By virtue of the above configuration, the energy storage element contains a gas soluble in the electrolyte in the case, and after the case is sealed, the gas dissolves in the electrolyte. As a result, the pressure inside the case decreases, creating a negative pressure inside the case, i.e., generating a force pulling the case inward, causing the gas present between the electrodes to be discharged to the outside of the electrode assembly. In a preferred embodiment, the electrode body is a wound electrode body having a pair of opposing curved portions and a flat portion located between the pair of curved portions, and the electrode body has a hollow region in the center when viewed from the winding axis direction, or there is a gap between the outer surface of the flat portion of the electrode body and the inner surface of the case, or a combination thereof. In a preferred embodiment, the main component of the electrolyte is carbonate, and the gas is carbon dioxide. In a preferred embodiment, the electrolyte contains an oxalate complex salt. In a preferred embodiment, the case has a flat, bottomed, rectangular cylindrical case body and a lid, and the electrode body is in direct or indirect contact with the inner surface of the case body. In a preferred embodiment, the case further includes a member capable of adsorbing the gas inside. In a preferred embodiment, the inside of the case has an atmosphere under a negative pressure of 0.02 MPa or more and 0.09 MPa or less (preferably 0.04 MPa or more and 0.07 MPa or less).
[0071] Next, a specific configuration example of an energy storage element according to one embodiment of the present invention will be described. FIG. 1 is a schematic exploded perspective view showing an electrode assembly and case of a nonaqueous electrolyte secondary battery as an energy storage element according to one embodiment of the present invention. FIG. 2 is a schematic cross-sectional view of the nonaqueous electrolyte secondary battery shown in FIG. 1. The energy storage element 1 includes an electrode assembly 2, a positive electrode current collector 4' and a negative electrode current collector 5' connected to both ends of the electrode assembly 2, respectively, and a case 3 that houses these. In addition, the electrode assembly 2 has a hollow region in a central portion 8, which is a configuration that can further enhance the effects of the energy storage element 1.
[0072] 1, the energy storage device 1 includes a case 3, an electrode assembly 2 housed in the case 3, and a positive electrode terminal 4 and a negative electrode terminal 5 provided on the case 3. The case 3 includes a case body 11 in the shape of a flat, bottomed rectangular cylinder, and a lid body 12 in the shape of an elongated rectangular plate that can close an elongated rectangular opening of the case body 11.
[0073] The lid 12 is provided with a positive electrode terminal 4 and a negative electrode terminal 5 that are electrically connected to the outside. The positive electrode is electrically connected to the positive electrode terminal 4 via a positive electrode current collector 4' that is connected to the positive electrode substrate, and the negative electrode is electrically connected to the negative electrode terminal 5 via a negative electrode current collector 5' that is connected to the negative electrode substrate.
[0074] The details of the electrode assembly, the electrolyte, the gas soluble in the electrolyte, the case, and the like that constitute the nonaqueous electrolyte secondary battery are as described above.
[0075] [Other embodiments] The energy storage device of the present invention is not limited to the above-described embodiment.
[0076] In the above embodiment, the description has been focused on the case where the energy storage element is a non-aqueous electrolyte secondary battery, but other energy storage elements may be used, such as capacitors (electric double layer capacitors, lithium ion capacitors).
[0077] Furthermore, although a wound electrode body is used in the above embodiment, a laminated electrode body formed from a laminate of a plurality of sheets each including a positive electrode, a negative electrode, and a separator may also be used.
[0078] Furthermore, in the above embodiment, the electrode body had a hollow region in the center, but the electrode body may also have an electrode body that does not have a hollow region in the center, or there may be a gap between the inner surface of the case body and the outer surface of the flat portion of the electrode body.
[0079] Furthermore, in the above embodiment, a non-aqueous electrolyte is used as the electrolyte for the non-aqueous electrolyte secondary battery, but the manufacturing method of the storage element can also be applied to nickel-metal hydride batteries and the like that use aqueous electrolytes. For example, in the case of the nickel-metal hydride battery, an alkaline solution such as a concentrated aqueous potassium hydroxide solution is used as the electrolyte. When the electrolyte is an aqueous electrolyte, examples of gases soluble in the electrolyte include ammonia (1 cm of water at 20°C under 1 atmosphere), 3 Solubility in 700cm 3 When the electrolytic solution is an aqueous electrolytic solution, examples of the gas that is poorly soluble or insoluble in the aqueous electrolytic solution include oxygen gas and nitrogen gas.
[0080] The present invention can also be realized as a power storage device including a plurality of the above-described power storage elements. Furthermore, a power storage unit can be configured by using one or more power storage elements (cells) of the present invention, and a power storage device can be configured by using this power storage unit. In this case, the technology of the present invention only needs to be applied to at least one power storage element included in the power storage unit or power storage device. The power storage device can be used as a power source for automobiles such as electric vehicles (EVs), hybrid vehicles (HEVs), and plug-in hybrid vehicles (PHEVs). Furthermore, the power storage device can be used in various power supply devices such as engine startup power supplies, auxiliary power supplies, and uninterruptible power supplies (UPS).
[0081] 3 shows an example of a power storage device 30 in which power storage units 20, each of which is an assembly of two or more electrically connected power storage elements 1, are further assembled. The power storage device 30 may include a bus bar (not shown) that electrically connects two or more power storage elements 1, and a bus bar (not shown) that electrically connects two or more power storage units 20. The power storage units 20 or the power storage device 30 may include a status monitoring device (not shown) that monitors the status of one or more power storage elements. [Example]
[0082] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0083] [Examples 1 to 2 and Comparative Examples 1 to 2] (1) Negative electrode formation process A negative electrode mixture paste containing non-graphitizable carbon as the negative electrode active material and polyvinylidene fluoride (PVDF) as the binder, with N-methyl-2-pyrrolidone (NMP) as the dispersion medium, was prepared. The ratio of the negative electrode active material to the binder was 93.0:7.0 by mass. The negative electrode mixture paste was applied to both sides of an 8 μm-thick copper foil substrate and dried to form a negative electrode mixture layer, thereby obtaining negative electrodes of Examples 1 to 2 and Comparative Examples 1 to 2. After drying, the amount of negative electrode mixture applied per unit area on one side (negative electrode mixture paste from which the dispersion medium had been evaporated) was 0.40 g / 100 cm. 2 It was made to be like this.
[0084] (2) Positive electrode formation process LiNi as a positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3A positive electrode mixture paste containing O2, polyvinylidene fluoride (PVDF) as a binder, and acetylene black as a conductive agent, and N-methyl-2-pyrrolidone (NMP) as a dispersion medium was prepared. The ratio of the positive electrode active material, binder, and conductive agent was 91.0:4.5:4.5 by mass. The positive electrode mixture paste was applied to both sides of an aluminum foil substrate with a thickness of 15 μm and dried to form a positive electrode active material layer, thereby obtaining positive electrodes of Examples 1 to 2 and Comparative Examples 1 to 2. After drying, the applied amount of the positive electrode mixture (the positive electrode mixture paste from which the dispersion medium has been evaporated) per unit area on one side was 0.86 g / 100 cm. 2 It was made to be like this.
[0085] (3) Electrode body formation process The electrode bodies of Examples 1 to 2 and Comparative Examples 1 to 2 were fabricated by stacking the negative and positive electrodes and a 21 μm-thick polyethylene separator and winding them around a hollow core. The hollow core was formed by heat-sealing a 150 μm-thick polypropylene sheet rolled into an elliptical cylindrical shape, resulting in a hollow region inside. Using such a hollow core, an electrode body was constructed in which a hollow region with an average thickness of 1 mm was formed in the center of the electrode body. The electrode body was wound to form a wound electrode body having a pair of opposing curved portions and a flat portion located between the pair of curved portions. The average thickness of the hollow region refers to the average length of the hollow region in the thickness direction of the electrode body (the Y-axis direction in FIG. 2 ).
[0086] (4) Electrode assembly housing process The electrode body was housed in a flat, bottomed, rectangular cylindrical case body made of aluminum alloy. In all of the energy storage elements of Examples 1 and 2 and Comparative Examples 1 and 2, the outer surface of the wound electrode body was in contact with the inner surface of the case body via a 150 μm thick insulating sheet made of polypropylene. (5) Electrolyte containing process For the energy storage elements of Example 2 and Comparative Example 2, a non-aqueous electrolyte solution was prepared by dissolving LiPF6 at 1.2 mol / L in a non-aqueous solvent in which PC, EMC, and DMC were mixed at a volume ratio of 30:35:35. For the energy storage elements of Example 1 and Comparative Example 1, a non-aqueous electrolyte solution was prepared by further dissolving lithium difluorobisoxalate phosphate [LiPF2(C2O4)2] as an additive in the non-aqueous electrolyte solution to a content of 0.5 mass%. Each of the prepared electrolyte solutions was placed in the case. 40 cm 3 The case has an internal volume of 120 cm 3 The volume of the electrode body is 50 cm 3 The sum of the volumes of the structures other than the electrode body (current collectors, etc.) and the electrolyte is 50 cm 3 In other words, the volume of the surplus space inside the case is 20 cm 3 It was. (6) Gas storage process After the electrolyte solution was placed in the storage element, preliminary charging was performed. Thereafter, in the energy storage elements of Examples 1 and 2, the pressure inside the case was reduced to 0.01 MPa using a vacuum pump, and then carbon dioxide gas, which is a gas soluble in the electrolyte solution, was injected at a rate of 18 cm. 3 The carbon dioxide gas contained 99.5% by volume of carbon dioxide, and contained nitrogen, oxygen, and methane as components other than carbon dioxide. In other words, the amount of gas soluble in the electrolyte was 89.5% by volume relative to the volume of the excess space in the case. The energy storage elements of Comparative Examples 1 and 2 were similar to the energy storage elements of Examples 1 and 2, except that air was contained in the case instead of carbon dioxide gas. (7) Sealing process Five minutes after the carbon dioxide gas or air was introduced into the case, the case was sealed by sealing the injection port, thereby obtaining test cells of nonaqueous electrolyte storage elements of Examples 1 and 2 and Comparative Examples 1 and 2. The pressure inside the case 48 hours after sealing was 0.06 MPa for Example 1, 0.11 MPa for Comparative Example 1, 0.06 MPa for Example 2, and 0.11 MPa for Comparative Example 2 at 25°C.
[0087] [evaluation] (Measurement of void volume of electrode body) After sealing, 48 hours later, the void volume of the electrode body of the energy storage elements of Examples 1 and 2 and Comparative Examples 1 and 2 was measured by the following procedure. (1) Obtaining a cross-sectional image of the electrode body A microfocus X-ray CT (Shimadzu inspeXio SMX-225CT FPD HR) was used to obtain cross-sectional images of the electrode body in the energy storage elements being measured. The conditions for obtaining the cross-sectional images were 3D CT imaging mode, image size of 512 pixels in both the vertical and horizontal directions, slice thickness of 77 μm, inter-slice distance of 77 μm, voxel size of 77 μm, field of view of 39.3 mmφ, and number of views of 1800. For each energy storage element, a cross-sectional image of the electrode body in the YZ plane was obtained, and the obtained cross-sectional images were saved as image files. (2) Cutting out the outline of the electrode body The outline of the electrode body was cut out from the obtained cross-sectional image of the electrode body using the image cutout function of the image editing software Adobe Photoshop Elements 11. (3) Binarization The void volume (number of pixels) of the electrode body was calculated using the image processing software WinROOF2013 for the cross-sectional image of the electrode body with the outline cut out. Here, the void volume was calculated for the portion of the cross-sectional image of the electrode body with the outline cut out, excluding the hollow region located in the center of the electrode body and the winding core. Specifically, a threshold value was set to a density 60% lower than the density at which the brightness intensity was maximum, and binarization processing was performed. On the side with low brightness density, pixel groups of 15 pixels or less were considered noise, and the void volume (number of pixels) of the electrode body was calculated by summing only pixel groups of 16 pixels or more. In addition, the reduction rate (%) of the void volume (number of pixels) of the electrode body due to the inclusion of carbon dioxide gas was determined by comparing the void volume (number of pixels) of the electrode body between Example 1 and Comparative Example 1, in which lithium difluorobisoxalate phosphate was added as an additive to the electrolyte, and Example 2 and Comparative Example 2, in which no additive was added. These evaluation results are shown in Table 1.
[0088] [Table 1]
[0089] FIG. 4 shows cross-sectional images of the electrode body in the XY plane of the energy storage elements of Examples 1 to 2 and Comparative Examples 1 to 2. As shown in FIG. 4, in the electrode bodies of Comparative Examples 1 and 2, which do not contain carbon dioxide gas, multiple areas where the inter-electrode distance is large are visually observed. On the other hand, in the electrode bodies of Examples 1 and 2, which contain carbon dioxide gas, the areas where the inter-electrode distance is large are reduced compared to Comparative Examples 1 and 2. Furthermore, unlike Comparative Examples 1 and 2, in the energy storage elements of Examples 1 and 2, the inner surface of the case body is recessed inward and contacts the outer surface of the flat part of the electrode body via an insulating sheet. When the inside of the case is in a negative pressure state, it is thought that the inner surface of the case body is recessed inward and contacts the outer surface of the electrode body, making it easier for gas that is difficult to dissolve in the electrolyte present between the electrodes to be discharged to the outside of the electrode body. Note that the cross-sectional images were obtained using a microfocus X-ray CT (inspeXio SMX-225CT FPD HR, manufactured by Shimadzu Corporation), as was used to calculate the void volume of the electrode body.
[0090] The void volume of the electrode body was measured using image processing. As shown in Table 1, in Examples 1 and 2, in which a gas soluble in the electrolyte solution was contained in the case, the void volume of the electrode body was significantly reduced compared to Comparative Examples 1 and 2, in which the gas was not contained in the case. This indicates that the energy storage element has a high effect of suppressing the increase in the inter-electrode distance. Furthermore, the reduction rate (%) of the void volume of the electrode body due to the addition of carbon dioxide gas was calculated between Example 1 and Comparative Example 1, in which lithium difluorobisoxalate phosphate was added as an additive to the electrolyte, and Example 2 and Comparative Example 2, in which the additive was not added. The reduction rate (%) of the void volume of the electrode body was greater in Example 1, in which the additive, which generates a large amount of gas such as carbon monoxide that is difficult to dissolve in the electrolyte, was added. This indicates that the effect of the energy storage element was enhanced when the additive, which tends to increase the inter-electrode distance, was included.
[0091] As described above, it is presumed that the manufacturing method of the energy storage element is highly effective in preventing the inter-electrode distance from becoming large. [Industrial Applicability]
[0092] The present invention is suitably used as an electricity storage element, including a non-aqueous electrolyte secondary battery used as a power source for electronic devices such as personal computers and communication terminals, automobiles, and the like. [Explanation of symbols]
[0093] 1. Energy storage element 2 Electrode body 3 cases 4 Positive terminal 4' Positive electrode current collector 5 Negative terminal 5' Negative electrode current collector 8 Central part 11 Case body 12 Lid 20 Energy storage unit 30 Electricity storage device
Claims
1. housing an electrode body in which the negative electrode and the positive electrode are stacked in a case; storing an electrolyte in the case; After the electrolyte is contained in the case, a gas soluble in the electrolyte is contained in the case; and a gas soluble in the electrolyte is contained in the case, the case is sealed, and an inside of the case is put into a negative pressure state; the gas soluble in the electrolyte is carbon dioxide; The time that elapses from the time when the gas soluble in the electrolyte is contained until the time when the case is sealed is within 30 minutes, A method for manufacturing an energy storage element, in which, after the case is sealed, the electrode body is pressed in a stacking direction by an inner surface of the case that is in direct or indirect contact with the electrode body.
2. The electrode body is a wound electrode body having a pair of curved portions facing each other and a flat portion located between the pair of curved portions, The method for manufacturing a storage element of claim 1, wherein after the electrode body is accommodated and before the case is sealed, the electrode body has a hollow region in the center when viewed from the winding axis direction, or a gap exists between the outer surface of the flat portion of the electrode body and the inner surface of the case, or a combination thereof.
3. 3. The method for producing an electric storage element according to claim 1, wherein the main component of the electrolyte is carbonate.
4. The method for producing a storage element according to claim 3, wherein the electrolyte contains an oxalato complex salt.
5. The case has a flattened rectangular cylindrical case body and a lid, The method for manufacturing an electric storage element according to claim 1 , wherein the electrode body is in direct or indirect contact with an inner surface of the case body after the case is sealed.
6. The method for manufacturing an energy storage element according to claim 1 , further comprising housing a member capable of adsorbing the gas in the case.
7. An electrode body in which a negative electrode and a positive electrode are laminated; An electrolyte; a gas soluble in the electrolyte; a sealable case for containing the electrode body, the electrolyte, and the gas; Equipped with the gas soluble in the electrolyte is carbon dioxide; The inside of the case has a negative pressure atmosphere of 0.02 MPa or more and 0.07 MPa or less, An energy storage element in which the electrode body is pressed in a stacking direction by an inner surface of the case which is in direct or indirect contact with the electrode body.
8. The electrode body is a wound electrode body having a pair of curved portions facing each other and a flat portion located between the pair of curved portions, The storage element of claim 7, wherein the electrode body has a hollow region in the center when viewed from the winding axis direction, or a gap exists between the outer surface of the flat portion of the electrode body and the inner surface of the case, or a combination thereof.
9. 9. The electric storage element according to claim 7, wherein the main component of the electrolyte is carbonate.
10. 10. The electric storage element according to claim 9, wherein the electrolyte contains an oxalato complex salt.
11. The case has a flattened rectangular cylindrical case body and a lid, 11. The energy storage element according to claim 7, wherein the electrode body is in direct or indirect contact with an inner surface of the case body.
12. The energy storage element according to claim 7 , further comprising a member capable of adsorbing the gas inside the case.
13. The method further includes: performing a preliminary charge after the electrolyte is contained in the case; and reducing the pressure inside the case after the preliminary charge is performed; The method for producing an electric storage element according to claim 1 , further comprising the step of: introducing a gas soluble in the electrolyte into the case after reducing the pressure inside the case.
14. 14. The method for manufacturing a storage element according to claim 1, wherein a gas soluble in the electrolyte is contained in the case so that the pressure inside the case immediately after the gas is contained is 0.1 MPa or more and 0.2 MPa or less.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery and method of manufacture
JP2003157898A
Electrolyte for nonaqueous electrolyte battery, and nonaqueous electrolyte battery
JP2007165125A
Power storage device and vehicle
JP2013143224A
Nonaqueous electrolyte secondary battery and manufacturing method therefor
JP2014123526A
Battery
JP2015092493A